2014
DOI: 10.7763/ijiet.2014.v4.437
|View full text |Cite
|
Sign up to set email alerts
|

Improving Female Student Retention in Computer Science during the First Programming Course

Abstract: Abstract-This paper is an evaluation study to improve female student retention in Computer Science during the first programming course. Although, colleges are using variety of ways to attract female students to continue their studies in Computer Science, the number of female students is decreasing in the major. Therefore, we have employed two survey studies to learn more about the lack of supported items in the major and tried to address most of those issues in the classroom to see the change in student's feel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…As a consequence, high dropout or failure rates in introductory programming courses are common. Students who do not succeed in such a course might quickly give up on the field of computing (Varol & Varol, 2014). To date, few studies have examined the role of programming self-efficacy in programming learning, especially as regards the relationship between persistence and programming self-efficacy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a consequence, high dropout or failure rates in introductory programming courses are common. Students who do not succeed in such a course might quickly give up on the field of computing (Varol & Varol, 2014). To date, few studies have examined the role of programming self-efficacy in programming learning, especially as regards the relationship between persistence and programming self-efficacy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature shows that students' perceptions of student-teacher relationships affect their motivation and engagement in instructional activities (Lazarides et al, 2018;Quin, 2017;Roorda et al, 2011;Xerri et al, 2018;Zhou et al, 2020). Varol and Varol (2014) found that a lack of communication between students and faculty is one of the leading causes of the underrepresentation of female students in the field of computer science. This study adds to the literature by examining the impact of students' perceptions of caring on students' successes in learning computer programming.…”
Section: Caringmentioning
confidence: 99%
“…Apesar dos resultados promissores obtidos com a realização das atividades apresentadas na Seção 4,é possível observar que a participação das meninas em maratonas de programação aindaé baixa, uma vez que poucas alunas do CIC/UnB interessaramse pelas competições em comparação a participação masculina. De acordo com [Varol and Varol 2014],é importante ter um ambiente confortável para as alunas, o qual torne a prática de preparos para competições viável. Portanto, com o objetivo de dar continuidade no oferecimento de um ambiente mais confortável para que as meninas sintam-se mais motivadas para aprender e desenvolver habilidades para as competições, pretende-se considerar mais atividades com foco em treinamento.…”
Section: Estratégias Propostas Para Atividades Futurasunclassified